Three-Dimensional Flow and Performance Simulation of Multistage Axial Flow Compressors - Li, Yiguang (Cranfield University, 2000)
\Yith the current develop111ent in computer technology and Computational Fluid D)"n<'tlllics techniques, t.he si11utlation within axial flow compressors becomes 1110re and 1110re pract.ical and beneficial to the compressor designs. Due to the insufficient capabilit)" of today's COll1put.ers for three-dimensional unsteady flow 1110delling of 111Ult i~Llg(' axial flow compressors, sophisticated models of steady state flow and perfor111ance 1110delling of the C0111prcssors deserve to be thoroughly investigated. In l1utltistage C0111pressor sinlulations with steady state methods, frame of reference is fixed on blades and the c0111putational domains for rotors and stators haye relati\"e rotation. One of the difficulties in such simulations is how to pass information across the interfaces between blade rows without losing continuity. Two 111ajor stead)" state modelling approaches, a mixing plane approach based on Denton's circu111ferentially non-uniform mixing plane model and a deterministic stress approach based on Adamczyk's average passage model, are investigated and compared with each other through the flow predictions of the third stage of Cranfield Low Speed Research Compressor at peak efficiency operating condition. In the deterministic stress approach, overlapped solution domains are introduced to calculate deterministic stresses in order to "close" the time-averaged governing equation system and the influence of the downstream blade row of the blade row under investigation has to be imposed through the simulation of bodyforce and blade blockage effect of the downstream blade row. An effective method of simulating bodyforce and blade blockage effect has been developed and proven to be simple in programming. ConYentionally, boundary conditions are specified in CFD calculations based on experimental data or other empirical calculations. By taking advantage of the special flow features in rear stages of multistage axial flow compressors where each rear stage behaves like a repeating stage of its neighbouring stages in terms of flow pattern at the inlet and the exit of these stages, a repeating stage model has been developed aiming at significantly simplifying the boundary conditions when simulating rear stages of a multistage axial flow compressor with only mass flow rate and stage exit average static pressure required as global input. A computer simulation system 1'/ STurbo3D has been developed to investigate a11d assess different steady state simulation models within multistage compressor environment. It has been proven that with the mixing plane model M STurbo3D is able to predict flows in multistage low speed axial flow compressors with acceptable accuracy. Application of the repeating stage model to the third stage of LS RC shows that the prediction with this model has equivalent accuracy to the prediction with the conventional boundary setting, and proves that the repeating stage model is an effective alternative to the expensive complete compressor simulation. The deterministic stress model provides more information of rotor-stator interaction and slightly better performance prediction than the mixing plane model, but the benefits of the model is not significant when applied to low speed axial flow compressors.